Analyzing Exposures to Electromagnetic Fields in an Intensive Care Unit - Gökmen, Necati (Turk J Anaesthesiol Reanim, 2016)
OBJECTIVE: In this study, we conducted a numerical analysis of exposure to electromagnetic fields (EMFs) in a hospital’s intensive care unit that is one of the most crucial one in terms of hazardous areas among all service units. This is a new study for measuring exposure to EMFs in an intensive care unit as well as other healthcare services in Turkey. METHODS: We measured the EMFs in the intensive care unit with a SRM-3006 (selective radiation metre), which was used for measurement of the absolute and the limit values of high frequency EMFs. The measurement points were chosen to represent the highest levels of exposure to which a person might be subjected. We obtained a dataset that included 5929 observations, with 96 extreme values, through measuring the magnetic field in terms of V/m. RESULTS: The measurements show the frequency varies from 47 MHz to 2.5 GHz as 17 frequency ranges at the measurement point as well. According to these findings, the referenced maximum safety limit was not exceeded. However, it was also found that mobile telecommunication was the most critical cause of magnetic fields. CONCLUSION: Further studies need to be performed with different frequency antennas to assess the EMFs in intensive care units.